2013
DOI: 10.1007/978-1-62703-330-5_16
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Melanocytes from Induced Pluripotent Stem Cells

Abstract: Epidermal melanocytes play an important role in protecting the skin from UV rays, and their functional impairment results in pigment disorders. Additionally, melanomas are considered to arise from mutations that accumulate in melanocyte stem cells. The mechanisms underlying melanocyte differentiation and the defining characteristics of melanocyte stem cells in humans are, however, largely unknown. In the present study, we set out to generate melanocytes from human iPS cells in vitro, leading to a preliminary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
2
31
0
1
Order By: Relevance
“…Experiments that examine the effects of candidate agents on melanocytes can be done in monoculture, human skin equivalents, or perhaps (in the future) in induced pluripotent stem cell derivatives. 32,36,149,150 Melanoma cell lines can be informative regarding the safety of prevention agents. Examples include the safety concerns raised for both NAC and vitamin E, both of which increased tumor cell motility and invasive capacity in vitro and in vivo.…”
Section: In Vitro Systemsmentioning
confidence: 99%
“…Experiments that examine the effects of candidate agents on melanocytes can be done in monoculture, human skin equivalents, or perhaps (in the future) in induced pluripotent stem cell derivatives. 32,36,149,150 Melanoma cell lines can be informative regarding the safety of prevention agents. Examples include the safety concerns raised for both NAC and vitamin E, both of which increased tumor cell motility and invasive capacity in vitro and in vivo.…”
Section: In Vitro Systemsmentioning
confidence: 99%
“…An embryoid body (EB)-based protocol was used to generate patient iMels; however, the differentiation efficiency of the conventional method (Ohta et al, 2011) was not satisfactory. In the conventional two-dimensional (2D) culture system, the majority of cells maintained an epithelial shape and were not differentiated into melanocytes ( Figures S2A-S2C).…”
Section: Suspensive System For Melanocyte Differentiationmentioning
confidence: 99%
“…More importantly, because genetically compatible iPSCs can be established from individual patients, drug screening could be performed within a personalized system to determine the most appropriate medical treatments for each of the affected individuals in the near future. Previous studies indicated that iPSCs can be differentiated toward the melanocyte lineage (Jones et al, 2013;Nissan et al, 2011;Ohta et al, 2011), and these human iPSC-derived melanocytes (hiMels) could express characteristic melanocytic markers, generate melanosomes, and integrate appropriately into the reconstructed epidermis in vitro. However, the in vivo functions and the hair follicle and epidermis reconstitution capability of hiMels have not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The model was used to assess the interactions of drug candidates with the SC‐based skin model. In another model, a vascularized SC‐based skin model was developed and connected to a neural network system to investigate the cross‐talk of the skin tissue with the sensory nerves via brain–skin neuroendocrine pathways . To model this interaction, peripheral neurons from iPSC‐derived neural SCs and Schwann cells were differentiated and incorporated into the skin model.…”
Section: Stem‐cell Based Organ‐on‐chip Platformsmentioning
confidence: 99%